PENERAPAN HUKUM ADAT DALAM PENYELESAIAN TINDAK PIDANA PERSETUBUHAN YANG DILAKUKAN OLEH ANAK DI WILAYAH HUKUMKABUPATEN LIMA PULUH KOTA SUMATERA BARAT - Wialanda Wiguna; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Settlement according to customary law in Minangkabau can be done in the Nagari Judiciary in thiscase carried out by Kerapatan Adat Nagari (KAN). KAN is a customary justice body in Minangkabau. Thetask is to resolve the Sako and Pusako disputes according to the provisions as long as the custom applies inthe Nagari, in the form of a peace decision, and also to settle the customary crimes that occur. However, theapplication of customary law in the jurisdiction of District Lima Puluh of West Sumatra City is still not fullyimplemented just because of a marriage ban on my neighbor, even though it is very contrary to the existingsanctions, if there is a case of intercourse, a mandatory sentence is to marry off the parties the problem.The purpose of writing this thesis are: First, To find out the process of resolving customary sexualintercourse criminal acts committed by children in the jurisdiction of Regency Lima Puluh of West SumatraCity Second, To find out the legal consequences that occur if the settlement of sexual intercourse is donethrough customary law in the jurisdiction Regency Lima Puluh City of West Sumatra.This type of research is a sociological juridical research which means an approach by looking interms of legislation and the reality that occurs in the field.From the results of the study concluded, First, the process of resolving the crimes of customary legalintercourse carried out by children in the jurisdiction of District Lima Puluh of West Sumatra City is not yetfully implemented, this is because if there is a ban on marriage to my neighbor so that customary settlementcannot be continued even though it is very contrary to the sanction of customary punishment that alreadyexists, that is if there is a case of intercourse, then the punishment that must be carried out is to marry offthe parties who are in trouble, are expelled from the village, and excommunicated from the community.Secondly, the legal consequences that occur if sexual intercourse is carried out through customary law inthe legal area of the District Lima Puluh of West Sumatra is that it can override criminal sanctions, becausethe customary sanctions imposed with the agreement of the adat authorities, the sanctions have the samevalid force as criminal law in the Criminal Code, because these sanctions are agreements that have beenestablished by previous adat leaders.Keywords: Application of Customary Law, Copulation and Children